Quality of working life: history, dimensions and benefits - Granados, Isabel (2011)
The purpose of this paper is to perform a theorical compilation of the history of the Quality of Working Life and the various concepts that have developed around it. In order to archive this, most relevant works are reviewed. Also, the two broad groups of dimensions that relate to QWL are examined: the objective and subjective conditions, each one of the components of both dimensions are outlined. Finally, the various benefits that come with the implementation of programs of QWL in the company are listed.